Formation mechanism of copper-gilded coronet ornaments excavated from a Sui or early Tang tomb situated in Xi’an, Shaanxi - Yanbing Shao; Fengrui Jiang; Junchang Yang; Quanmin Zhang; Xuan Lu; Wenbin Fu; Sumei Yu (Heritage Science, 2023)
Abstract The formation of the gold layer in mercury gilding occurs through the heating a gold amalgam. As a result, the formation mechanism and technical characteristics of gilded products are closely related to the temperature at which they are heated. In this study, XRD and XPS analysis of a copper-gilded coronet from the Sui or Tang dynasties revealed that Au3Cu was one of the main phases of the gold layer. Therefore, base on the thermodynamic stability of ordered phases like Au3Cu, the estimated heating temperature for this copper-gilded coronet ranged from 240 to 285 ℃. Furthermore, SEM–EDS analysis of the cross-sectional concentration distribution of Cu indicated that the diffusion distance of Cu during heating did not exceed 2 μm. At 240–285 ℃, Cu diffused along the defects of the gold layer, and the diffusion process followed Fick’s second law. Previous research has indicated that the defect path diffusion coefficient of Cu is on the order of 10–12 cm2/s, and the heating time of the gilding process is typically considered to be 15 min. Using the diffusion equation, the calculated diffusion distance of Cu aligned with the diffusion behavior of Cu at 240–285 ℃, confirming the inferred heating temperature range. Additionally, at these temperatures, the gold layer was formed through the solid-state reaction of the gold amalgam and was bonded to the substrate through the diffusion of Cu.